Feasibility of assessing symptoms associated with ovarian cancer using an electronic medical intake questionnaire - Eric D. Helm; Cam Nguyen; Stephen Rotholz; Saketh R. Guntupalli; Barbara A. Goff; Benjamin G. Bitler; Kian Behbakht (Gynecologic Oncology Reports)
Objective: Symptoms occur in up to 75% of patients with early-stage ovarian cancer; as such, using a symptom inventory (SI) to stratify which patients should receive screening for ovarian cancer is an attractive approach to mitigate false-positives. We report on the feasibility and results of a prospective four-question SI that assessed the following symptoms: abdominal pain, bloating, early satiety, and urinary complaints. Frequency and duration of symptoms were not assessed. Methods: A SI was added to the standard pre-appointment check-in process via the electronic medical record’s (EMR) patient portal for all annual or new patient visits in a generalist obstetrics and gynecology faculty practice in patients over 40 years of age. IRB exemption was granted. Data were extracted from the EMR, compiled in REDCap, and analyzed in R. Results: A total of 589 individual patients were included in the final analysis. The median age of the participants was 50 years (range: 40–86). 27.8 % of patients experienced at least one symptom in the prior year, and the most commonly reported symptom was urinary urgency/frequency (14.9 %). Patients with a history of medical comorbidities such as depression, uterine fibroids, endometriosis, and irritable bowel syndrome were more likely to screen positive on the SI. No cancers have been diagnosed to date. Conclusions: Implementing a SI using the EMR is feasible but is influenced by the presence of pre-existing diagnoses. The effectiveness of an EMR-based SI pre-screen as a selection criterion for early detection requires further study and assessment of frequency and duration of symptoms should be considered.